DISENTANGLING THE SHARED HERITABILITY OF THE PREDISPOSITION TO HYPERTENSION AND TYPE 2 DIABETES. (June 2022) - Timasheva, Yanina; Balkhiyarova, Zhanna; Prokopenko, Inga
Abstract : Objective: Genome-wide association studies (GWAS) identified over 900 genetic loci for blood pressure traits and over 200 for type 2 diabetes (T2D). Hypertension and T2D often manifest in the shared setting of metabolic syndrome, which also includes obesity, hyperlipidemia, and increased coagulability. We aimed to dissect shared genetic factors contributing to the comorbidity of these conditions using multi-phenotype approach. Design and method: Using GWAS summary statistics, we defined 1, 855 single nucleotide variants (SNVs) associated with 17 endophenotypes related to blood pressure, T2D, and glycaemic traits. We identified 242 T2D association signals represented by 561 T2D/glycaemic SNVs overlapping with 1189 SNVs associated with blood pressure trats and located within 100 kb distance. Using hierarchical clustering, we defined groups of shared loci affecting circadian rhythm (MTNR1B), cell-mediated autoimmunity (CDKAL1 and G6PC2), insulin signalling and cell metabolism (KCNJ11), cell cycle regulation and apoptosis (BCL2), inflammation, calcium ignalling and regulation of eating behavior (NUCB2). Results: We identified 35 signals associated with two or more cardiometabolic phenotypes, including rs560887 in G6PC2 gene related to higher fasting glucose levels pulse pressure (PP); rs7756992 in CDKAL1 leading to elevated systolic blood pressure (SBP), increased T2D risk, but lower body mass index (BMI); rs635634 in ABO influencing many metabolic endophenotypes, most notably leading to increased risk of T2D and stroke; rs5219 in KCNJ11 increasing risk of T2D, related to elevated SBP and PP; and rs12454712 in BCL2 related to higher SBP and abdominal obesity, and to lower T2D susceptibility and lower BMI. Using functional enrichment analysis, we identified pathways significantly associated with hypertension, T2D, and glycaemic traits. Top associated pathways included detection of stimulus involved in sensory perception (GO:0050906), sensory perception of chemical stimulus (GO:0007606), detection of chemical stimulus involved in sensory perception (GO:0050907), sensory perception of smell (GO:0007608), detection of chemical stimulus involved in sensory perception of smell (GO:0050911), and detection of chemical stimulus (GO:0009593). Conclusions: Our results highlight the shared pathways involved in blood pressure and glucose metabolism regulation and the development of T2D, suggesting common biological mechanisms. The study was supported by the megagrant from the Government of Russian Federation No. 075-15-2021-595